"Thank You for Being Republican": Negotiating Science and Political Identities in Climate Change Learning. Issue 1 (2nd January 2018) - Walsh, Elizabeth M.; Tsurusaki, Blakely K.
Abstract : When engaging with socioscientific issues, learners act at the intersection of scientific, school, and other societal communities, drawing on knowledge, practices, and identities from both in and out of the classroom to address problems as national or global citizens. We present three case studies of high school students whose classroom participation in a unit on the politically polarizing topic of climate change was informed by their political identities and how they situated themselves in climate change's sociocultural, historical, and geologic context. We describe how these students, including two who initially rejected human-influenced climate change but revised their understandings, negotiating dissonant identities in the classroom through repeated engagement with conflicting political and scientific values, knowledge, and beliefs. These case studies problematize building bridges between formal and informal learning experiences and suggest that it may be necessary to leverage disconnections in addition to building connections across settings to promote productive identity work. The results further suggest that supporting climate change learning includes attending to identity construction across ecosocial timescales, including geologic time.